Cytological and Histopathological Spectrum of Histoplasmosis: 15 Years of Experience in French Guiana - Drak Alsibai, Kinan; Couppié, Pierre; Blanchet, Denis; Adenis, Antoine; Epelboin, Loïc; Blaizot, Romain; Louvel, Dominique; Djossou, Félix; Demar, Magalie; Nacher, Mathieu (Frontiers in Cellular and Infection Microbiology, 2020)
Background Disseminated histoplasmosis remains a major killer of immunocompromised patients in Latin America. Cytological and histological methods are usually present in most hospitals and may represent a precious diagnostic method. We report 15 years of experience of the department of pathology of the Centre Hospitalier de Cayenne Andrée Rosemon in French Guiana. Methods Specimens from live patients from January 2005 to June 2020 with the presence of H. capsulatum on cytological and/or histological analysis were analyzed. All specimens were examined by an experienced pathologist. The analysis was descriptive. Results Two hundred two cytological and histological samples were diagnosed with histoplasmosis between January 2005 and June 2020. The 202 samples included 153 (75.7%) histopathological formalin-fixed and paraffin-embedded tissues (biopsy or surgical specimens) and 49 (24.3%) cytological analysis from all organs. One hundred thirty-four patients (82.7%) were HIV-positive, 15 patients (9.3%) had immunosuppressant treatment, and 13 patients (8%) were immunocompetent. Seventy-eight of 202 (38.5%) were samples from the digestive tract, mostly the colon (53/78 cases, 70%) and small intestine (14/78 cases, 18%). Microorganisms were more numerous in digestive samples (notably the colon) than in other organs. Lymphocyte and histiocyte inflammation of moderate to marked intensity were observed in all positive specimens. Tuberculoid epithelioid granuloma were present in 16/78 (20,5%) specimens including 14 colon and 2 small intestine specimens. There were 11/202 cases of liver histoplasmosis, 26/202 (12,8%) cases of pulmonary histoplasmosis. Bone marrow involvement was diagnosed in 14 (2%) specimens (8 aspiration and 6 biopsies). Lymph nodes were positive in 42 specimens (31 histology and 11 cytology). Histopathological analysis of the 31 lymph nodes showed a variable histological appearance. Tuberculoid forms were most frequent (24/31, 77,4%). Conclusions From the pathologist perspective, this is the largest series to date showing that digestive involvement was the most frequent, usually with a tuberculoid form and a greater load of Histoplasma. With awareness and expertise, cytology and pathology are widely available methods that can give life-saving results in a short time to help orient clinicians facing a potentially fatal infection requiring prompt treatment.